RUNNING TIME ALGORITHM SEARCHING DATA IN ONE DIMENSION ARRAY USING JAVA NETBEANS - jOHNSON SIHOMBING (INFOKOM (Informatika & Komputer), 2018)
Data search algorithms are often used in any programming consisting of: sequentialsearching, binary searching and interpolation searching.Search data can be done in an array, either one-dimensional array, two dimensional andeven n-dimensional. For the research, the author only do the implementation of searchalgorithm on a one dimensional array that each data element is numeric type.The search process is performed on consecutive and non-sequential data in the array.Unassisted data can be found in sequential searches. The opposite is true for binarysearch and interpolation search.The purpose of implementing the algorithm is to show the difference of the result of therunning time of the three search algorithms above, which can be visualized in graphicalform.The results are obtained after the authors perform the implementation of searchalgorithm by using a desktop-based Java software with editor or compiler Netbeans 8.1.